Borrowing in the Novel “The Good Earth” and It’s Translation Into “Bumi Yang Subur”: Borrowing in the Novel “The Good Earth” and It’s Translation Into “Bumi Yang Subur” - Ni Nyoman Ayu Tri Hidayanti; I Made Juliarta (Focus Journal : Language Review, 2022)
The translation is done by transferring form of the first language to the form of the second language using of semantic structure. It must be transferred and held constant and the form may change. But translation activities do not only deal with transferring language from one language to another language, but also deal with the most important thing, such as; message and meaning from source language to target language. This study analyzed about types of borrowing are found in the translation of The Good Earth into Bumi yang Subur. The library research method and field research method used in this study. The description of the method can be seen in the following explanations. This study used library research. In this type of research, the location is very flexible. The research was done every where as long as the place supports the main facility needed such as books and computer. Types of borrowing found in the data source are pure borrowing, naturalized borrowing and cultural borrowing.